Myocardial native T1 mapping and cardiac outcomes in thalassemia major. (8th February 2021) - Meloni, A; Martini, N; De Luca, A; Positano, V; Pistoia, L; Gerardi, C; Sanna, PMG; Bitti, PP; Benni, M; Sorrentino, F; Sinagra, G; Pepe, A
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): The E-MIOT project receives "no-profit support" from industrial sponsorships (Chiesi Farmaceutici S.p.A. and ApoPharma Inc. and Bayer). Background. The T2* cardiovascular magnetic resonance (CMR) is the gold standard for the non invasive detection of myocardial iron overload (MIO). The native myocardial T1 mapping has been proposed as a complementary tool, thanks to its higher sensitivity in presence of small amounts of iron, but no data are available in literature about its clinical impact. Objective: To explore the clinical impact of T1 mapping for detecting cardiac complications in thalassemia major (TM). Methods. We considered 146 TM patients (87 females, 38.7 ± 11.1 years) consecutively enrolled in the Extension-Myocardial Iron Overload in Thalassemia Network. Three parallel short-axis slices of the left ventricle (LV) were acquired with the Modified Look-Locker Inversion recovery (MOLLI) sequence. The native T1 values in all 16 myocardial segments were obtained and the global value was the mean. Results. Twenty-one patients had an history of cardiac complications: 11 heart failure, 8 arrhythmias (7 supraventricular and 1 ventricular), and 2 pulmonary hyperthension. Patients with cardiac complications had significantly lower global heart T1 values (879.3 ± 121.9 ms vs 963.2 ± 98.5 ms; P < 0.0001) (Figure) but comparable T2* values (33.32 ± 11.66 ms vs 37.17 ± 9.15 ms; P = 0.116). Cardiac complications were more frequent in the group of patients with reduced global heart T1 value (<928 ms for males and <989 ms for females) compared to the group with normal global heart T1 value (71.4% vs 39.5%; P = 0.009). Odds ratio (OR) for cardiac complications was 3.8 (95%CI = 1.3-10.9) for patients with reduced global heart T1 value versus patients with normal global heart T1 value. Conclusion: We found out a significant association between decreased native global heart T1 values and a history of cardiac complications, suggesting that an early detection of myocardial iron burden by native T1 can support the clinicians in modifing chelation therapy earlier.